Identification of three mutatons in the cyp21 gene in Vietnamese patients having signs of congenital adrenal hyperplasia - Viet, Le Bac; Phuong Mai, Nguyen Thi; Hoang, Nguyen Huy (Academia Journal of Biology, 2013)
Congenital adrenal hyperplasia (CAH) is a disease causing disorders in adrenal steroid hormone metabolism, above 90% cases are derived from 21-hydroxylase deficiency. The loss or reducing of this enzyme activity leads to accumulating of intermediate precusor (progesterone and 17-hydroxyprogesterone) in adrenal gland metabolism, resulting in overproduction of androgen which causes virilization signs in patients. In this study, we utilized MLPA (multiplex ligation probe amplification) technique, PCR (polymerase chain reaction) and entire CYP21A2 gene sequencing method to detect mutations. The CYP21A2 gene analysis results from two female patients identified three mutations, including 30 kb deletion mutation, I2 splice mutation and g.1584delA in exon 7 of the CYP21A2 gene. The mutation g.1584delA is responsible for transcated protein of 21-hydroxylase, therefore this enzyme is impaired completely. These results proved the correlations between genotype and phenotype of patients having signs of CAH and based on them, doctors can bring out useful genetic consultants as well as therapy treatments for patients.